FORMATION OF RESEARCH CULTURE OF STUDENTS IN THE TEACHING OF PHYSICS IN HIGHER EDUCATION - Alimbekova, Г.Б.; Turganova, М.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In the article the possibilities of development of research culture of studentsof non-skew professional pedagogical education. The research culture of students is a brief description of his level of qualification for his selfsocialization, his abilities, skills and knowledge. He also demonstrates that education, knowledge, and skills in research culture the basis for the training of future teachers and are important for the development of the individual. Scientific - research culture of students of non-spry professional pedagogical education.